Taboo: Sex, identity, and erotic subjectivity in anthropological fieldwork - Kulick, Don; Willson, Margaret (Routledge, 1995)
Taboo looks at the ethnographer and sexuality in anthropological fieldwork and considers the many roles that sexuality plays in the anthropological production of knowledge and texts. How does the sexual identity that anthropologists have in their "home" society affect the kind of sexuality they are allowed to express in other cultures? How is the anthropologists' sexuality perceived by the people with whom he or she does research? How common is sexual violence and intimidation in the field and why is its existence virtually unmentioned in anthropology? These are but a few of the questions to be confronted, exploring from differing perspectives the depth of the influence this tabooed topic has on the entire practice and production of anthropology. A long-overdue text for all students and lecturers of anthropology, many post-fieldwork readers will find a resonance of issues they have previously faced (or tried to avoid) and those who are still to undertake fieldwork will find articles that refer to other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.
Keywords: anthropologie; discipline; identités; ressource en ligne; sciences humaines; sexualité; thématiques; violences; violences sexuelles

Emprise et violence maternelles: étude d'anthropologie psychanalytique - Couchard, Françoise (Dunod, 1991)
A partir d'exemples culturels et de cas empruntés à la clinique quotidienne, cet ouvrage montre les effets psychologiques d'une réduction de la personnalité féminine à sa seule fonction de reproduction : en particulier les comportements d'agression de la mère vis-à-vis de sa ou de ses filles.
Keywords: 1900-1999; anthropologie; cours; discipline; europe; fem1000; figure de la mère; france; maternité; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; violences familiales